Performance of Modified Natural Zeolites by Sodium Hydroxide Treatments in The Esterification of Glycerol and Oleic Acid - Rizky Achmad Fauzi; Silvester Tursiloadi; Adid Adep Dwiatmoko; Dede Sukandar; Fauzan Aulia; Nino Rinaldi; Sudiyarmanto Sudiyarmanto (Jurnal Kimia Valensi, 2019)
Esterification is the reaction of the formation of an ester compound by reacting an alcohol compound and carboxylic acid. In this study, the performance of zeolite-based catalysts has been studied for esterification reactions. Modification of zeolite pore size was done to be hierarchical zeolite, with the aim of increasing the catalytic properties of zeolite. The modification was carried out by desilication by sodium hydroxide treatment with a variation of 0.1; 0.3; 0.5 M. The resulting catalyst was then characterized using BET and XRD. Furthermore, the catalyst was tested for activity for esterification of fatty acids and glycerol and the product was analyzed using GC-MS. Zeolite modification with sodium hydroxide has been proven to improve catalyst performance, without changing their crystal structure. The best catalytic activity was obtained on the catalyst with sodium hydroxide treatment of 0.3 M, resulting glycerol conversion of 92% and selectivity to monoglycerides of 74%.